2005
DOI: 10.1111/j.1440-1746.2005.03578.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term recurrent abdominal pain related to Helicobacter pylori infection in children

Abstract: H. pylori infection is more commonly found in children with short-term RAP, and presentation of epigastric pain in these cases can be considered as a warning alarm to screen for H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
5
16
3
1
Order By: Relevance
“…Abdominal pain is the main gastrointestinal complaint in preschool and school children with a prevalence of about 10% (1). In the present study, the prevalence of RAP in children was 9.3%; in some previous studies this ranged from 10% to 15% among 4-16-year-old children (6,14).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Abdominal pain is the main gastrointestinal complaint in preschool and school children with a prevalence of about 10% (1). In the present study, the prevalence of RAP in children was 9.3%; in some previous studies this ranged from 10% to 15% among 4-16-year-old children (6,14).…”
Section: Discussionsupporting
confidence: 44%
“…Helicobacter pylori infection commonly occurs in childhood and lasts for a number of years (1,4,5,8).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence shows that the prevalence of H. pylori was significantly higher among children with reflux oesophagitis than in children with hyperemic gastropathy [31] . However, we could not find any significant difference between H. pylori positive and negative cases in the incidence of nausea, and vomiting [32] , or diarrhea [33] . However, other studies reported positive correlation between the infection and diarrhea [3,18] , and in some cases it correlates with vomiting [3] .…”
Section: Patientscontrasting
confidence: 80%
“…15,30,40 However, we did not find any significant difference in the incidence of nausea, 37 or diarrhea. 35 Other studies reported positive association between diarrhea and H. pylori infection in children. 16,30 Comparison between HP positive cases and HP negative cases revealed a statistically significant difference in the incidence of iron deficiency anemia (p=0.025).…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry mentioning
confidence: 99%
“…Epigastric pain as a localizing symptom associated with H. pylori infection has been documented in other studies as well. 6,[35][36][37] However, epigastric pain was less frequently encountered in the study by Kalach et al 38 Upper GI endoscopy and biopsy was carried out in 10 children with persistent epigastric pain and vomiting. It revealed a significantly higher incidence of nodular gastritis in H. pylori infected cases especially among older children (p<0.05), and indicates histopathological evolution of the lesions with chronicity of infection.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry mentioning
confidence: 99%